Patient experiences with handling of analgesic transdermal patches and challenges in correct drug administration: a pilot study on patient education - Lampert, Anette; Keßler, Jens; Washington-Dorando, Phoebe; Bardenheuer, Hubert J.; Eknes, Emilia Bocek; Krisam, Johannes; Haefeli, Walter E.; Seidling, Hanna (Journal of patient safety, 2018)
BackgroundAlthough problems during transdermal patch administration are primarily caused by insufficient knowledge, patient education programs are lacking. We compared patient education by a clinical pharmacist on knowledge on correct patch administration with routine counseling during patient-physi
Gesehen am 04.11.2019